Simulation of mixing different temperature jets using CABARET method - Zaitsev, Aleksey Mikhailovich; Semenov, Vladimir Nikolaevich; Shvetsov, Yuriy Evgenievich (Computational Continuum Mechanics, 2013)
Mathematical modeling of mixing jets with different temperatures discharged from the fuel assemblies of a sodium-cooled fast-neutron reactor BN is presented. Numerical simulations are performed using the CABARET method. The aim is to verify the applicability of the CABARET method to the calculations of liquid flows with a small Prandtl number (~ 0.01) at relatively high Reynolds numbers (~105). For this purpose, the fluid flowing through the geometrically complex channel of the experimental setup has been investigated. Mesh decomposition and finite-difference grid generation techniques are described. The comparison between the numerical and experimental data shows that with the proposed approach the time-averaged local temperatures in the non-isothermal flow of liquid metal can be predicted with a sufficient accuracy, and a good qualitative description of the pulsation characteristics of the flow can be provided.
Keywords: LES; mesh decomposition; pulsation characteristics of the flow; CABARET technique; liquid metal cooled reactor; mixing of jets with different temperatures